Relational Job Characteristics and Well-Being of Brazilian K-12 Teachers - Klein, Natan (2023)
A teacher’s relationship with students can be a source of more than stress. The attributes of relational jobs either promote positive (e.g., work engagement) or inhibit negative (e.g., exhaustion) psychological states that constitute potential predictors of teachers’ general well-being (e.g., health perception). The present study tests hypotheses regarding the relationships between the psychological effects of relational job characteristics and teachers’ work-related and context-free well-being indicators. Preschool, primary, and secondary Brazilian school teachers (n = 2205) responded to a cross-sectional survey. Data were analyzed by multiple mediator structural equation modeling. The psychological effects of relational job characteristics predicted exhaustion, engagement, and health perception. Findings support indirect effects on health perception of exhaustion and engagement. Data were interpreted according to the job demands-resources model, where the relational job characteristics constitute essential resources that foster work engagement, diminish burnout, and indirectly affect more generalized well-being states such as general health. Possible explanations for the relationships are discussed.